Avaliação farmacológica da membrana de PVA [Poli (álcool-vinil)] associada a arnica e à laserterapia no processo cicatricial de lesão cutânea causadas por queimaduras - Cardoso, Carolina Silva (2023)
The organ most affected by burns is the skin and initial care differs according to the degree of injury. Second-degree burns require greater care, as the damage is more extensive and worrisome and the use of a biomaterial can help in the cell repair process, with better planning, low cost and better accessibility. Arnica extract has proven anti-inflammatory and analgesic properties in the treatment of skin lesions. With the advent of laser therapy, and proven biomodulation of the inflammatory process in second-degree burns, it is yet another therapeutic alternative for skin lesions. Objective: To evaluate the pharmacological effects of arnica extract incorporated into PVA [poly (vinyl alcohol)] in a delivery system associated with lowintensity laser on second-degree burns. Material and Methods: Pure PVA membranes (PVA) or PVA with 5% arnica extract (PVA+A) were resistant and characteristic (physical-chemical methods) for application in skin lesions. Through in vivo studies, the effects of PVA and PVA+A membrane dressings, with or without the application of low-intensity laser (L), on 2nd degree burns in Wistar rats, which enabled histological analyzes (Hematoxylin-eosin and Masson's Trichrome) and immunohistochemistry [markers: CD68, smooth method alpha actin (a-SMA) and fibronectin] in the different experimental groups. Results: With regard to obtaining and characterizing, we have that: the thermogravimetry curve showed that the addition of arnica to the PVA matrix did not alter the thermal resistance of this polymer; differential scanning calorimetry demonstrated that the addition of arnica subtly increased the crystallinity value of the PVA+A sample when compared to the PVA sample; in the mechanical tensile test, after the addition of arnica, a reduction in the value of the elastic modulus was observed, in relation to the PVA; in the Fourier Transform Infrared spectroscopy it was observed that there was no interaction between the arnica molecules and the PVA chains; in the swelling test, the presence of arnica reduced the swelling capacity of the membrane. The controlled release profile of arnica showed a rapid release into the medium in up to 9 hours and a sustained release until the end of the test. In in vivo studies, with regard to tissue repair, the PVA+A+L group made it possible to identify more collagen fibers than in the control group (p<0.05), whereas with immunohistochemical markers the highlight was with a-SMA, where the PVA and PVA+L groups showed an increase in myofibroblasts (p<0.05). Both the increase in the number of collagen fibers and myofibroblasts accelerate the healing process, thus reducing tissue repair time. Conclusion: The incorporation of arnica extract to PVA was biocompatible and with sustained release of the active in an effective way, being a promising dressing option for skin lesions. Through this study, we also reiterate that low-intensity laser therapy with or without arnica was effective in accelerating the healing process, due to its potential biomodulator effect, improving inflammatory aspects, as well as conditioning collagen fibers, promoting rapid healing in skin lesions